Incentives and practice improve prospective memory performance in older adults - Menéndez-Granda, Marta; Schmidt, Nadine; Orth, Michael; Horn, Sebastian; Kliegel, Matthias; Peter, Jessica (Aging clinical and experimental research, 2025)
Background Prospective memory can decline with age. Incentives or practice may improve it. Previous research indicated that avoiding financial losses may be more appealing for older adults than achieving financial gains. Aims In this study, we examined whether financial gains, financial losses, or practice will improve prospective memory performance in older adults. We included N = 132 healthy adults (60–80 years old, 35% female). Methods We used a between-subject factor ‘group’ (event-based or time-based prospective memory; financial gains or losses) and a within-subject factor ‘practice’ comprising 2 blocks (first or second half of task trials). All participants performed a 1-back task as an ongoing task and a prospective memory task embedded in the 1-back task. We used linear effects modelling to examine whether incentives or practice improved task accuracy, response times, or clock checking. Results The prospect of financial losses accelerated event-based prospective memory responses and led to more strategic clock checking in the time-based prospective memory task compared to the prospect of financial gains. In addition, it accelerated ongoing task responses compared to financial gains. Practice, in contrast, only improved event-based prospective memory with no effect on time-based prospective memory. Conclusions Our findings highlight the importance of choosing an incentive adjusted to the performance outcome when designing studies that examine the influence of incentives or practice on prospective memory.